First record of the genus Uroxys Westwood, 1842 in Martinique (Lesser Antilles), with descriptions of two new species from cloud forests (Coleoptera: Scarabaeidae: Scarabaeinae) - Huchet, Jean-Bernard; Coulis, Mathieu; Lamy, Fabrice; Touroult, Julien (Zootaxa, 2026)
Two new species of Uroxys Westwood, 1842 are described from Martinique: Uroxys martinicensis Huchet, sp. nov., and Uroxys aphanes Huchet, sp. nov. These species represent the first documented presence of Uroxys in Martinique. Both new species are flightless due to their brachypterous condition (reduced metathoracic wings), a condition that highlights the role of the cloud forests of the Lesser Antilles as centers of endemism and attests to the long-term isolation of some insular lineages of Scarabaeinae. These new taxa are compared with the three other Uroxys species currently known from the Lesser Antilles, namely U. vincentiae Arrow, 1903, U. productus Arrow, 1933, and U. trinitatis Arrow, 1933, and diagnostic characters are provided. An identification key to the Uroxys species from the Lesser Antilles is provided, along with two distribution maps: one detailing the Martinican records of the new taxa, and another summarizing the distribution of the genus across the archipelago.